Nonlinear seismic analyses of historical Topuzlu Dam under different seismic loads - Sayin, Erkut; Karaton, Muhammet; Calayir, Yusuf (Croatian Soc Civil Engineers-Hsgi, 2016)
The nonlinear analysis of historical Topuzlu Dam under various seismic loads is presented in this study, taking into account the solid-fluid interaction. The smeared crack model, which includes strain softening, is used to examine nonlinear behaviour of the dam material. The reservoir and soil domains are assumed to be linearly elastic. The ANSYS finite element program is used for generation of solutions.
Keywords: solid-fluid interaction; smeared crack model; artificial accelerograms; nonlinear seismic analysis